Thioglycoligase derived from fungal GH3 β-xylosidase is a multi-glycoligase with broad acceptor tolerance - Manuel Nieto-Domínguez (Nature Portfolio, 2020)
Thioglycoligases have proved useful for bonding carbohydrates to non-sugar acceptors, however, the scope of these biocatalysts is usually limited. Here, the authors engineer a xylosidase into a thioglycoligase with the ability to form O-, N-, S- and Se- glycosides together with sugar esters and phosphoesters.